Beta-Cell Specific Deletion of Dicer1 Leads to Defective Insulin Secretion and Diabetes Mellitus - Kalis, Martins (Public Library of Science, 2011)
Mature microRNAs (miRNAs), derived through cleavage of pre-miRNAs by the Dicer1 enzyme, regulate protein expression in many cell-types including cells in the pancreatic islets of Langerhans. To investigate the importance of miRNAs in mouse insulin secreting β-cells, we have generated mice with a β-cells specific disruption of the Dicer1 gene using the Cre-lox system controlled by the rat insulin promoter (RIP). In contrast to their normoglycaemic control littermates (RIP-Cre(+/−) Dicer1 (Δ/wt)), RIP-Cre(+/−) Dicer1(flox/flox) mice (RIP-Cre Dicer1 (Δ/Δ)) developed progressive hyperglycaemia and full-blown diabetes mellitus in adulthood that recapitulated the natural history of the spontaneous disease in mice. Reduced insulin gene expression and concomitant reduced insulin secretion preceded the hyperglycaemic state and diabetes development. Immunohistochemical, flow cytometric and ultrastructural analyses revealed altered islet morphology, marked decreased β-cell mass, reduced numbers of granules within the β-cells and reduced granule docking in adult RIP-Cre Dicer1 (Δ/Δ) mice. β-cell specific Dicer1 deletion did not appear to disrupt fetal and neonatal β-cell development as 2-week old RIP-Cre Dicer1 (Δ/Δ) mice showed ultrastructurally normal β-cells and intact insulin secretion. In conclusion, we have demonstrated that a β-cell specific disruption of the miRNAs network, although allowing for apparently normal β-cell development, leads to progressive impairment of insulin secretion, glucose homeostasis and diabetes development.